2015
DOI: 10.1080/02640414.2014.979857
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heavy resistance exercise on repeated sprint performance in youth athletes

Abstract: This investigation assessed whether prior heavy resistance exercise would improve the repeated sprint performance of 16 trained youth soccer players (Age 17.05 ± 0.65 years; height 182.6 ± 8.9 cm; body mass 77.8 ± 8.2 kg). In session 1, individual 1 repetition max was measured utilising a squat movement. In sessions 2 and 3, participants performed a running-based repeated anaerobic sprint test with and without prior heavy resistance exercise of 91% of their 1 repetition max. Times were recorded for each of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Previous studies have demonstrated an acute improvement of sprint performance after PAP in athletes of various sports disciplines (Bevan et al, 2010;Seitz et al, 2014;Chatzopouloset al, 2007;McBride et al, 2005;Rahimi, 2007;Yetter and Moir, 2008;Evetovich et al, 2015;Low et al, 2014). Moreover, PAP resulted in improved RSA (best sprint time and mean sprint time) in handball athletes (Okunoet al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have demonstrated an acute improvement of sprint performance after PAP in athletes of various sports disciplines (Bevan et al, 2010;Seitz et al, 2014;Chatzopouloset al, 2007;McBride et al, 2005;Rahimi, 2007;Yetter and Moir, 2008;Evetovich et al, 2015;Low et al, 2014). Moreover, PAP resulted in improved RSA (best sprint time and mean sprint time) in handball athletes (Okunoet al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…The paper published by Low (2015) presented the findings from the study aimed at verification whether resistance training with high load would improve sprint speed in young soccer players (Low et al 2015). The study examined 16 young players, who had performed barbell squats for at least 6 previous months.…”
Section: The Impact Of Pap On Speed Abilities In Soccermentioning
confidence: 99%
“…The studies used the load intensity from 70% to 91% in 1RM (6,8,13,(28)(29)(30)(31)(32)(33)(34)(35). Two studies (5,22) used the load intensity of 3RM, and one study (7) used 5RM.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…No heterogeneity was observed (I 2 = 24.35%, P = 0.252) between the studies ( Figure 2B). Four studies evaluated the sprint time in the final distance of 31 to 40 meter (22,28,29,34). The study by Rahimi et al (29), included the data of PAP with load intensities of 70% of 1RM (n = 11) and 85% of 1RM (n = 11).…”
Section: Meta-analysismentioning
confidence: 99%